Stroke and atrial fibrillation: is stroke prevention treatment appropriate beforehand?. Issue 5 (1st November 1999) - Deplanque, D; Corea, F; Arquizan, C; Parnetti, L; Mas, J L; Gallai, V; Leys, D
Abstract : OBJECTIVE: To undertake a pilot study before conducting a large European multicentre prospective study, to determine the proportion of patients with atrial fibrillation who were not receiving antithrombotic treatment before stroke onset, and their characteristics. DESIGN AND PATIENTS: The stroke in atrial fibrillation ensemble (SAFE) I study was an observational study conducted in 213 patients with atrial fibrillation consecutively admitted in 1997 to three European centres for an acute stroke or transient ischaemic attack (TIA). It was determined whether they were receiving prior antithrombotic treatment. RESULTS: Atrial fibrillation was known before stroke in 148 patients (69.5%). Of 213 patients, 34 (16.0%) were receiving anticoagulation treatment before stroke, but only six had an international normalised ratio between 2.0 and 3.5; 65 (30.5%) were receiving antiplatelet treatment; and three (1.4%) were receiving both anticoagulation and antiplatelet treatment. Of 137 patients eligible for oral anticoagulation, 108 (78.8%) did not receive treatment. Of 142 patients eligible for any antithrombotic treatment, 62 (43.7%) were not treated. The logistic regression analysis, assuming anticoagulation treatment as a dependent variable, found digoxin treatment, absence of arterial hypertension, mitral stenosis, and cardioversion as independent factors. Assuming any antithrombotic treatment as a dependent variable, previously known atrial fibrillation, lower age, being a non-smoker, and absence of arterial hypertension were found to be independent factors. CONCLUSION: More than half of the patients with atrial fibrillation admitted for acute stroke or TIA were not receiving any antithrombotic treatment beforehand. New onset atrial fibrillation and contraindications account for a minority of non-prescriptions; thus, other reasons should be identified to improve stroke prevention in the community.